Implementation of Problem Based Learning Model to Measure Communication Skills and Critical Thinking Skills of Junior High School Students (Journal of Innovative Science Education, 2019)
Learning also needs to be directed to familiarize students to formulate problems, not only solve problems. In addition, the learning done must train critical thinking skills not just thinking mechanically. The US-based Partnership for 21st Century Skills (P21), identifies the competencies needed in the 21st century namely "The 4Cs" - communication, collaboration, critical thinking, and creativity. Science learning was developed as an integrative science subject, namely integrating applicative biology, physics and chemistry to develop thinking skills, expressing skills and developing innovating and collaborating skills. To improve critical thinking skills, creative thinking, communication, and collaboration, of course, the teacher must have the right model or method. PBL is a model that begins with a case and problem that has a goal so that students can solve the problem. This study aims to determine the profile of communication skills and critical thinking skills of students. Research carried out using the type of descriptive research with the method used is a qualitative method to observe critical thinking skills, creative, communication, and collaboration in science learning. The data taken was the result of observation of communication skills, the results of tests of critical thinking questions, and interviews of Muhammadiyah 4 Semarang Junior High School students as many as 9 research subjects. The profile of students' communication skills was assessed from the results of observations during the last six meetings. The scores were averaged 55.56% with very high categories, namely SP1, SP2, SP3, SP5, SP6 and 44.44% of high-category students namely SP4, SP7, SP8, SP9. The results of the observations were also supported by the results of interviews of students from SP1 to SP9 which showed a correspondence with the scores obtained. The profile of students' critical thinking skills is assessed from the results of tests of critical thinking when the final learning material is obtained 11.11% is very high category, namely SP1; 33.33% of high category students, namely SP2, SP3, SP4; and 55.56% in the medium category, namely SP5, SP6, SP7, SP8, SP9. The results of the tests of critical thinking are also supported by the results of interviews of students from SP1 to SP9 which indicate the existence of correspondence with the scores obtained.